Shifts in the Heart Left Ventricle Function in Patients with Pulmonary Tuberculosis During Adequate Chemotherapy - A. E. Dityatkov; A. E. Radzevich; V. A. Tikhonova; N. I. Kobakhidze (Антибиотики и Химиотерапия, 2020)
To investigate the hemodynamics and myocardic contraction of the heart left ventricle, 61 patients with pulmonary tuberculosis (main group) and 26 healthy subjects (control group) were observed. Higher ultimate systolic and diasystolic volumes of the left ventricle and lower levels of the efflux fraction in the patients with active pulmonary tuberculosis were stated. There was shown inverse correlation of the systemic systolic arterial pressure and the left ventricle efflux fraction with ESR, evident of the tuberculosis intoxication. The most pronounced aggravation of the left ventricle function was recorded in the patients with the most severe tuberculosis process. The impairments in the left ventricle in the patients with active pulmonary tuberculosis were of functional nature. Due to intensive therapy of the tuberculosis, the indices of the left ventricle efflux function improved and the systemic arterial pressure came to normal, along with elimination of the tuberculosis intoxication signs.